Pengaruh Model Student Facilitator and Explaining (SFE) dengan Media Peta Konsep Terhadap Keterampilan Berbicara Peserta Didik di SDN 09 Pontianak Barat - Suriyani, Suriyani; Razi, Fahrul; Resvan, Resvan (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2025)
The Effect of Student Facilitator and Explaining (SFE) Model with Concept Map Media on Speaking Skills of Students at State Elementary School 09 West Pontianak. Faculty of Tarbiyah and Teacher Education Study Program Madrasah Ibtidaiyah State Islamic Institute (IAIN) Pontianak. 2024. This study was motivated by the lack of speaking skills of students when performing in front of the class. The speaking skills of students here are still quite lacking and must continue to practice continuously. The purpose of this study was to determine the effect of using the student facilitator and explaining (sfe) model with concept map media on the speaking skills of fourth grade students at SDN 09 West Pontianak. To achieve these objectives, researchers used experimental research methods using Trueexperimental quantitative approach. The population in this study were all students of class 4C and 4D which amounted to 50 people. Then sampling was carried out using saturated sample technique so that the samples used were class 4C as a control class totaling 25 students and 4D as an experimental class totaling 25 students. Data collection tools in the form of storytelling essay test questions to test the speaking skills of students before and after applying the student facilitator and explaining (sfe) learning model with media map concept. The results showed: (1) The speaking skills of grade IV students of SDN 09 West Pontianak before applying the student facilitator and explaining (sfe) learning model with concept map media get an average score of 67.4 in the moderate category. (2) The speaking skills of grade IV students of SDN 09 West Pontianak after using the student facilitator and explaining (sfe) learning model with concept map media get an average score of 85.4 in the high category. (3) There is a significant effect of 0.200 from the use of student facilitator and explaining (sfe) learning model with concept map media on the speaking skills of grade IV students of SDN 09 West Pontianak. (4) There is an influence between the student facilitator and explaining (sfe) learning model with concept map media on the speaking skills of class IV students of SDN 09 West Pontianak with a value of 0.8 in the high category.